Die Betrachtung der Schnelligkeit im Kontext der konditionellen Fähigkeiten und die Notwendigkeit einer neuartigen Sichtweise - ein Modellansatz zur Strukturierung der Schnelligkeit - Damerow, M. (2006)
Measurable conditional and coordinative skills, in context with other components, define the power of sport. Conditional skills such as power, endurance, speed or flexibility, as well as coordinative skills like the processes of the regulation of movement, never appear as isolated single skills; they always appear in combinations. The coherence and the structure of conditions, which define the prerequisites of the power of sport, are thus so comprehensive and interconnected that it seems to be hard to overlook and to understand their complexity. Additionally, the conditional skill speed has such a complex structure integrated within the power of sport. She is together with power, endurance and flexibility one part of the conditional skills. But on the other hand do different facts as well as survey results question that speed is to be considered simply as a conditional skill. KAROß, KÖNIG, SIMSHÄUSER (1994, 122) and also THIENES (1998) and LÜHNENSCHLOß a. O. (1997) criticise that and reference to the coordinative character of speed. This characteristic appears to play the major part in the capacity of speed. The different concepts which say speed is a conditional or a coordinative skill are the foundation of that dissertation. The opinion of a technical-coordinative character of speed is reflected in the major hypothesis. The intention of the sportscientific paper is the characterisation of speed as an technical-coordinative prerequisite for power with the help of descriptive statistics. Basically it is questioned that speed is further a conditional prerequisite. That means that it is necessary to reconsider definitions and declarations of the athletic speed and its classification in existing models of the performance of the sport. There are also two other criteria which have to be awarded as another peculiarity to the speed. On the one hand, there is speed of movement with maximum rate and on the other hand there is a non fatigue process for 5 to 8 seconds after the start (ROTH 1982, BADTKE 1999). Such a course without any fatigue and endurance needs to be questioned also in the opinion of MESTER (1991), LÜHNENSCHLOß (1999) and RÖCKER (2002). Reasons for those doubts are output losses in the level of further jumps (MESTER 1991), the loss of speed during sprints (LÜHNENSCHLOß 1999) as well as the residues in the process of exhalation (RÖCKER 2002). No movement of speed exists without the loss of power. Endurance is everytime a part of the rapidity of movement. Keeping that assumption in mind has the characterisation of speed and the integration in a structure of conditional skills no validity anymore. Furthermore do we have to consider speed as a form of endurance. With the opinion that endurance has a foundational character for every movement, there are propositions to structure and modelling speed. The leading position of endurance of speed during maximum movement has to be specificated and also finds integration within the posted models. The important results and expertises of this paper can be summed up as followed: speed is able to be characterized with the elementary, coordinative, and determined prerequisite of power, as well as through the processes of energy supply. The visual action is the quickness and the accuracy of a movement which is the complex result of steering and energy delivering bodily functions. It is not possible to say speed is only an power factor of condition or co-ordination. The performances of speed presented in form of speed movement are determined with the help of prerequisite performances, which either use one factor (condition, coordination) more than the other. Because of this, they are not able to act independent from each other. The character of co-ordination appears to be leading. For example do the reaction, frequency and sequence belong to the coordinative power. The results of the energy process in the fast movement are power of strength. Therefore they are conditional skills. The power of speed as the tempo of movement has been signed of complex basics. Those basics are facts of the complex of condition and co-ordination. But one of them is leading. So the facts don`t work independent. For example, has the power of speed, the endurance of speed and the process of speeding up a conditional character but the complex reaction and the frequency of steps are more coordinational determinated. Many empirical data from the lateral and the longitudinal research of the school of sport in Magdeburg are only interpretable with the fact of fatigue. With these data it is possible to verify, that next to the conditional loss of power, the coordinational determinated fatigue is taking place first. A pilot study proved such loss of power and fatigues in high frequency motorical moves. The opinion of speed without fatigue and loss of power within the first 5 seconds of movement have been destroyed.